Investigating the Prevalence of Neurological Soft Signs in Children with Autism Spectrum Disorder and their Siblings: A Cross-Sectional Study - Razjouyan, Katayoon; Babazadeh dezfoly, Abbas; Davari Ashtiani, Rozita; Khademi, Mojgan; Arabgol, Fariba; Nasiri, Mohammad Javad; Piri, Nahid; Miri, Mohammad Ali (Iranian Journal of Child Neurology, 2025)
Objectives Autism is determined by children’s inability to communicate with others through language. More studies have shown that neurological soft signs (NSS) can be one of the symptoms of psychiatric disorders, including schizophrenia. However, complete and proven evidence regarding the role of NSS in the pathogenesis of autism has not been determined. For this purpose, this research investigated the prevalence of NSS in children with autism spectrum and their siblings and compared it with the control group. Materials & Methods The current study was cross-sectional. In this study, thirty-two children aged 7-17 who had been referred to the pediatric psychiatry clinics of Imam Hossein Hospital and the Autism Charitable Association in Tehran, Iran, were entered; they were diagnosed with an autism disorder by a child and adolescent psychiatrist based on the DSM-5 diagnostic criteria. Furthermore, thirty-two siblings of children with autism in the age group of 7-17 years who did not have any neurological and mental disorders were included; thirty-two healthy individuals (controls) who did not have any disorders were evaluated with the K-SADS checklist. Gilliam Autism Rating Scale 3rd Edition (GARS-3) was also used to confirm the diagnosis and severity of the disease. Results The results showed that the incidence of NSS in the patient group was higher than in the other two groups, which was statistically significant (p<0.05). Furthermore, the results indicated that these signs had a high diagnostic value in identifying patients from healthy people. Conclusion In general, using the NSS score in patients with autism can be considered a prediction factor compared to their siblings. In addition, the score had no effect on the prediction between sibling and control subjects